2016
DOI: 10.18203/issn.2454-2156.intjscirep20160715
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between vaginal and abdominal hysterectomy in non-descent cases

Abstract: INTRODUCTIONHysterectomy, abdominal, vaginal or laparoscopic assisted vaginal hysterectomy is the most commonly performed elective major gynaecological surgery. 1 The current ratio of abdominal to vaginal hysterectomy is 3:1 for the treatment of benign disorders. The ratio should be reversed because fewer post-operative complications are associated with the vaginal route, which allows earlier recovery and return to work. 2Vaginal Hysterectomy is a technique that had already been introduced and performed centur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 5 publications
2
7
0
Order By: Relevance
“…11 Chavhan RP et al, reported fever in 24% vs 16% cases, UTI in 4% vs 8% cases, paralytic ileus in 8% vs nil in TAH and NDVH group respectively. 23 Abrol S et al, reported fever in 26% vs 6% cases, UTI in 6% vs 2% cases,and paralytic ileus in 6% vs nil in TAH and NDVH group respectively. 24 In the present study, author found wound infection rate in the TAH group to be 6% with no cases in NDVH group.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…11 Chavhan RP et al, reported fever in 24% vs 16% cases, UTI in 4% vs 8% cases, paralytic ileus in 8% vs nil in TAH and NDVH group respectively. 23 Abrol S et al, reported fever in 26% vs 6% cases, UTI in 6% vs 2% cases,and paralytic ileus in 6% vs nil in TAH and NDVH group respectively. 24 In the present study, author found wound infection rate in the TAH group to be 6% with no cases in NDVH group.…”
Section: Discussionmentioning
confidence: 93%
“…25 Chavhan RP et al, stated that there is one case of bowel injury in TAH group. 23 Mehta K et al, reported one case of bladder injury in NDVH group and one case of bowel injury in TAH group and 4 cases of ureteric injury in TAH group. 11 In this study, the Mortality rate was also nil in both the study groups.…”
Section: Discussionmentioning
confidence: 99%
“…On extensive review of literature and comparison of all the parameters with other studies, our results were comparable to other studies. 1,2,[4][5][6][7] NDVH was found to be safe and effective operative technique for benign gynaecological conditions and should be offered whenever possible, considering safety, better operative outcome and cost effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…They return to normal day to day activities faster, as the recovery time is shorter than those undergoing abdominal surgeries. 2 It also offers better functional capacity and improved pain assessment. The American college of Obstetricians and Gynecologists committee opinion recommends the vaginal https://doi.org/10.18231/j.ijogr.2020.032 2394-2746/© 2020 Innovative Publication, All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation